Humanistic training and soft skills in university students - Sotelo de Mendiola, Rosalía Jesús (2018)
This research had as objective to find out what university students know about humanistic training and soft skills in the development of their professional career, for which, the following hypothesis was raised: The students from the Universidad Nacional del Centro del Perú have little knowledge about humanistic training and soft skills in the development of their professional career. The method used was the descriptive–explanatory one. From the results it was obtained that 51 % of the respondents are male, and the 49 %, female; most of the respondents are under 23 years old, and attend eighth, ninth and tenth semesters. It was concluded that university students do know about humanistic training and soft skills; however, studies carried out by prestigious institutions point out that graduates do not have the "soft" skills, such as ethical sense or adaptability, while students think that is not their problem but the lack of specialized knowledge, and that the separation between humanities and sciences is only an anachronism and today’s world demands interdisciplinarity, since current problems are unresolved from a single perspective.   DOI: https://doi.org/10.31876/sl.v1i1.4